Seasonality of tuberculosis: the reverse of other respiratory diseases in the UK. Issue 9 (September 1996) - Douglas, A. S.; Strachan, D. P.; Maxwell, J. D.
Abstract : BACKGROUND: In Western societies there is a winter peak in mortality, largely accounted for by respiratory and cardiovascular deaths. In view of the known seasonal variation in vitamin D, and of the postulated link between tuberculosis and vitamin D deficiency, a study was undertaken to examine whether the presentation of tuberculosis had the same seasonal rhythm as other pulmonary infections. METHODS: Using cosinor analysis the presence or absence of seasonality was determined for 57, 313 tuberculosis notifications for England and Wales. OPCS data in four weekly notifications over a 10 year period (1983-92) were examined as two quinquential sets (1983-7 and 1988-92). These were compared with two groups of acute respiratory illness: 138, 992 notifications to OPCS of pneumonia deaths for 1988-92 and all admissions to Scottish hospitals with respiratory disease (252, 163 cases) during 1980-4. RESULTS: Analysis of notifications of tuberculosis revealed a summer peak with an amplitude of 10%. This pattern differs markedly from other respiratory disorders in which a winter peak and summer trough is observed. CONCLUSIONS: The unusual seasonality of tuberculosis is currently unexplained. One possibility is that low post-winter trough levels of vitamin D (which are known to affect macrophage function and cell mediated immunity) might result in impaired cellular immunity leading, after a latent period, to reactivation of dormant mycobacterial infection.